Healthcare in Turkey: from laggard to leader. (21st January 2011) - Baris, Enis; Mollahaliloglu, Salih; Aydin, Sabahattin
Abstract : Enis Baris and colleagues observe that a political commitment to universal health coverage together with a significant investment in health has seen Turkey's health indicators catch up and surpass other middle income countries